Kebutuhan Hierarki Tokoh Ningrum Dalam Novel Perempuan Bayangan Karya Netty Virgiantini - Bekti Setyo Ningrum; Vita Alfiyana; Eva Dwi Kurniawan (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research aims to determine the love and affection needs of the character Ningrum in the novel Perempuan Shadow using the humanistic psychological theory of hierarchy of needs by Abraham Maslow. The problem formulation for the novel Perempuan Shadow by Netty Virgiantini is the research object because based on the author's observations, no researcher has analyzed this novel specifically using a literary psychology approach. The method applied in this research is qualitative descriptive analysis. The results of this research are physiological needs, security needs, love and affection needs for the character Ningrum in the novel Perempuan Shadow, but the needs for self-esteem and self-actualization have not been found in the character Ningrum in the novel Perempuan Shadow.